Comparative Genomics of DNA Recombination and Repair in Cyanobacteria: Biotechnological Implications - Cassier-Chauvat, Corinne; Veaudor, Théo; Chauvat, Franck (Frontiers in Microbiology, 2016)
Cyanobacteria are fascinating photosynthetic prokaryotes that are regarded as the ancestors of the plant chloroplast; the purveyors of oxygen and biomass for the food chain; and promising cell factories for an environmentally friendly production of chemicals. In colonizing most waters and soils of our planet, cyanobacteria are inevitably challenged by environmental stresses that generate DNA damages. Furthermore, many strains engineered for biotechnological purposes can use DNA recombination to stop synthesizing the biotechnological product. Hence, it is important to study DNA recombination and repair in cyanobacteria for both basic and applied research. This review reports what is known in a few widely studied model cyanobacteria and what can be inferred by mining the sequenced genomes of morphologically and physiologically diverse strains. We show that cyanobacteria possess many E. coli-like DNA recombination and repair genes, and possibly other genes not yet identified. E. coli-homolog genes are unevenly distributed in cyanobacteria, in agreement with their wide genome diversity. Many genes are extremely well conserved in cyanobacteria (mutMS, radA, recA, recFO, recG, recN, ruvABC, ssb and uvrABCD), even in small genomes, suggesting that they encode the core DNA repair process. In addition to these core genes, the marine Prochlorococcus and Synechococcus strains harbor recBCD (DNA recombination), umuCD (mutational DNA replication), as well as the key SOS genes lexA (regulation of the SOS system) and sulA (postponing of cell division until completion of DNA reparation). Hence, these strains could possess an E. coli-type SOS system. In contrast, several cyanobacteria endowed with larger genomes lack typical SOS genes. For examples, the two studied Gloeobacter strains lack alkB, lexA and sulA; and Synechococcus PCC7942 has neither lexA nor recCD. Furthermore, the Synechocystis PCC6803 lexA product does not regulate DNA repair genes. Collectively, these findings indicate that not all cyanobacteria have an E. coli-type SOS system. Also interestingly, several cyanobacteria possess multiple copies of E. coli-like DNA repair genes, such as Acaryochloris marina MBIC11017 (2 alkB, 3 ogt, 7 recA, 3 recD, 2 ssb, 3 umuC, 4 umuD and 8 xerC), Cyanothece ATCC51142 (2 lexA and 4 ruvC) and Nostoc PCC7120 (2 ssb and 3 xerC).